(3GdeYdheGJjI hMVGQI GdYhdeI (B:s (3QDjI JbOjQjI YQHjI (B/s - (3jGSjf, GdSjOs ((3GdbGgQI(B: s (3OGQ GdfgXI ddWHGYI hGdfTQ(B, s, 2001)
(3JLO aj gPG GdcJGH (B: (3KhQI GdeYdheGJjI ,GdYQH Ydi eTGQa GdCdajI GdKGdKI , GdfbO hGdfbO GdPGJj ,GdeSJbHdjGJ hGdTHGH GdYdej ,GdYQH hJMOjGJ eLJeY GdeYQaI,GdJbOe hGdEHOGY GdMVGQjs
Keywords: (3GdYdGbGJ GdOhdjIs; (3GdYhdeIs; (3GdeYdheGJs